Subgrain characterization of low carbon copper bearing steel under plane strain compression using electron backscattered diffraction - Pawan Kumar (AIMS Materials Science, 2023)
The restoration mechanism (RM) and subgrain characteristics of 0.05C-1.52Cu-1.51Mn steel in single-hit plane strain compression (PSC) were investigated using a thermomechanical simulator (Gleeble). It was observed that at diminished deformation temperature (DT) and larger strain rate, the austenitic phase (during deformation) showed some thermal/dynamic softening (TH/DRS), but it did not reach the condition where the "work hardening rate" (WH rate)became constant with the stress, i.e., dynamic recovery (DRV) softening balances work hardening (WH). However, it was observed that at higher DT and lower strain rate, the "WH rate" for samples deformed at 850 ℃ (at a strain rate of 0.01 s−1), 950 ℃ (at strain rates of 0.1 and 0.01 s−1) and 1000 ℃ (at strain rates of 0.1 and 0.01 s−1) increased to negative peak, and then decreased to almost zero (for samples deformed at 950 and 1000 ℃ at a strain rate of 0.01 s−1), which is the onset of steady-state flow. When the sample deformed at 750 ℃ followed by quenching, the microstructure was indicative of a deformed microstructure rather than a transformed microstructure. It was observed that there was an increase in the extent of substructure formation and a decrease in mean subgrain size with increasing strain rate. When samples deformed at 850,950 and 1000 ℃, these temperature ranges were above Ar3 temperature. Hence quenching would lead to a phase transformation and hence the deformed microstructure would be eliminated. The room temperature microstructures when the sample deformed at a strain rate of 1 s−1, were nicely equiaxed and clean with no dislocations present. However, at lower strain rates of 0.1 and 0.01 s−1, microstructure showed substructures.